Isolation and multilocus genotyping of Toxoplasma gondii in seronegative rodents in Brazil - Araujo, Jacqueline B.; da Silva, Aristeu V. [UNESP]; Rosa, Ronaldo C.; Mattei, Rodrigo J.; da Silva, Rodrigo C. [UNESP]; Richini-Pereira, Virginia B. [UNESP]; Langoni, Hélio [UNESP] (Elsevier B.V., 2010)
Synanthropic rodents, mainly rats and mice, become ecologically associated with men due to changes in their ecosystems caused by human activities. These animals may take part in the epidemiological cycles of several diseases, including toxoplasmosis. The presence of serum antibodies to Toxoplasma gondii in 43 rodents captured in the urban area of Umuarama, PR, Brazil, was verified by modified agglutination test (MAT). Brain and heart samples were also collected and bioassayed in mice for the isolation of the parasite. Isolated samples were analyzed by 12 multilocus genotyping. Although all rodents were seronegative, the parasite was isolated in one mouse (Mus musculus) and one rat (Rattus rattus). Genotyping showed that these samples were similar to those previously isolated from cats in the state of Parana, Brazil. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Toxoplasmosis; Mus musculus; Rattus rattus; Antibody detection; Bioassay; Genotyping